The Attenuated Effects of Topical Empagliflozin on Imiquimod-induced Model of Psoriasis in Mice: The attenuated effects of Topical Empagliflozin on Imiquimod-induced Model of Psoriasis in Mice - Abbas , Alaa H.; Abbas, Zahraa H; Salman, Hayder Ridha; Jabar, Hayder E; H. Abd, Abdulkareem (Journal of Tropical Life Science, 2024)
Empagliflozin is a sodium-glucose cotransporter inhibitor (SGLT2) that drops blood glucose levels by inhibiting glucose reabsorption and encouraging glucose excretion. Other benefits of empagliflozin include cardiovascular protection, lowering uric acid levels, and reducing liver damage brought on by non-alcoholic fatty liver disease (NAFLD). to investigate the possible influence of two different concentrations of empagliflozin gel on psoriasis induced via imiquimod in mice. dividing 40 mice into five groups (8 mice for each group). All groups gated imiquimod to induce psoriasis (except group I) for seven days. The induction group (Group II) received imiquimod cream for seven days. The rest of the groups gated Clobetasol propionate cream 0.05%, empagliflozin 1% gel, and empagliflozin 3% gel, respectively, once daily for seven days after seven days of induction by imiquimod. The outcomes exhibited that topical empagliflozin had important anti-psoriatic activity by diminishing the Psoriasis Area Severity Index (PASI) score and improving histological alterations during imiquimod application; moreover, it elevated anti-inflammatory biomarker IL-37 and lowered inflammatory biomarkers TNF-α and IL-17. Empagliflozin has substantial anti-psoriatic action against imiquimod-induced psoriasis through its anti-proliferative and anti-inflammatory effects. Also, empagliflozin has a restorative effect on the histopathological alterations of mice's skin induced by imiquimod